2022
DOI: 10.1101/2022.02.01.478694
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Collaborative Cross strains and their founders vary widely in cocaine-induced behavioral sensitization

Abstract: Cocaine use and overdose deaths attributed to cocaine have increased significantly in the United States in the last 10 years. Despite the prevalence of cocaine use disorder (CUD) and the personal and societal problems it presents, there are currently no approved pharmaceutical treatments. The absence of treatment options is due, in part, to our lack of knowledge about the etiology of CUDs. There is ample evidence that genetics plays a role in increasing CUD risk but thus far, very few risk genes have been iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Further evidence for a genetic basis of cocaine use was the observation that an acute dose of the drug caused significant differences in locomotor activity across 45 inbred mouse strains (Wiltshire et al, 2015). Divergence in sensitization to cocaine was also found using 51 genetically diverse collaborative cross strains and their inbred founders (Schoenrock et al, 2022). An elegant study using two closely related substrains of the C57BL/6 mouse strain revealed that a missense mutation in Cyfip2 results in altered sensitization to cocaine (Kumar et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Further evidence for a genetic basis of cocaine use was the observation that an acute dose of the drug caused significant differences in locomotor activity across 45 inbred mouse strains (Wiltshire et al, 2015). Divergence in sensitization to cocaine was also found using 51 genetically diverse collaborative cross strains and their inbred founders (Schoenrock et al, 2022). An elegant study using two closely related substrains of the C57BL/6 mouse strain revealed that a missense mutation in Cyfip2 results in altered sensitization to cocaine (Kumar et al, 2013).…”
Section: Introductionmentioning
confidence: 99%